VIOLENT RELAXATION IN ISOLATED STAR CLUSTERS - B. Shukirgaliyev; A. Otebay; A. Just; P. Berczik; Ch. Omarov; A. Naurzbaeva; M. Kalambay (Academic Scientific Journal of Computer Science, 2019)
We study the effect of initial mass function and stellar evolution on the survivability of isolated star clusters after instantaneous gas expulsion. Our model clusters form with a centrally peaked star-formation efficiency profile according to the local-density-driven cluster formation model. We perform direct N body simulations of 104 N star clusters with global star-formation efficiencies ranging from 0.13 to 0.50. We have found that the stellar evolutionary mass-loss does not affect the number of bound stars of star clusters with high global SFE ( 0.2 gl SFE ), and the decrease in final bound mass fraction is only due to stellar evolution. But star clusters with lower global SFE are affected more by stellar evolutionary mass-loss and survive with less number of stars than if it would consist of single-mass non-evolving stars. High-SFE clusters also do not expand much after violent relaxation, while clusters with 0.15 gl SFE and 0.20 expand significantly. The global SFE as low as 0.30 gl SFE is sufficient for a cluster to almost keep its mass and size at the time of gas expulsion in our models.